Analysis of Elderly Activity in Elderly Posyandu Services - Surani; Agung Wibowo (Asian Journal of Healthcare Analytics, 2022)
The Elderly Posyandu is a health service built independently by the community under the responsibility of the village head. This research uses a descriptive qualitative approach (Cresweel, 2012). With 152 elderly subjects in Gading Jaya village. The data analysis was based on the recapitulation of the Posyandu data for the elderly in January-June 2022. The data analysis described the activities of the elderly based on spiritual factors, education, work, and family. The results show that the level of education and occupation of the elderly causes activity in posyandu services to be still low, only 17%, and in the elderly who have a high and high school education and middle economic level.